JULIANA JAYA AS A SEWING COURSE CENTRE TO ENHANCE LOCAL FASHION CREATIVITY - Azizah, Wala (Universitas Negeri Yogyakarta, 2025)
This research is driven by the critical role that sewing course centres play in enhancing local fashion creativity while preserving cultural heritage through the education of practical skills. The purpose of the study is to examine how Juliana Jaya, as a sewing course centre, contributes to the development of local fashion creativity and community empowerment. The methodology employed is qualitative research, utilising a case study approach, which involves participants, instructors, and local stakeholders as the sample. Data collection techniques include semi-structured interviews, participant observation, and review of course documents. The principal results indicate that Juliana Jaya effectively integrates modern sewing skills with local cultural values, creating a learning environment conducive to creative exploration and fashion innovation. The major conclusion highlights the centre’s central role in preserving cultural identity while promoting the growth of the local creative economy. This study contributes by providing a community empowerment model and strategies for integrating cultural technology in local fashion education.